Pharmacological aspects of hydrazides and hydrazide derivatives - Abidov, Musa (Health Promotion & Physical Activity, 2017)
Intense search for new antimicrobials, including anti-tuberculosis drugs, is dictated by the phenomenon of bacterial multidrug resistance. Hydrazides are considered the key intermediate and valuable starting material for some novel biologically active compounds. Over 70% of recently reported synthetic hydrazide derivatives are evaluated for antimicrobial and/or antifungal activity. The most frequently applied hydrazide is an anti- tuberculosis drug isoniazid/isonicotinic acid hydrazide (NIH). Hydrazide chemicals are sharing a common functional group characterized by a nitrogen- to-nitrogen covalent bond with four substituents with at least one of them being an acyl group, whereas the related hydrazines do not carry an acyl group. Hydrazides can be further classified by atom attached to the oxygen: carbohydrazides, sulfonohydrazides, phosphonic dihydrazides, hydrazone-hydrazides and phthalhydrazides. In addition to their antibacterial and antifungal activities, hydrazide derivatives have recently attracted continuing interest because of their anti-inflammatory properties. A phthalhydrazide derivative tamerit/galavit has been successfully introduced for human therapies.